ASSESSMENT OF THE FINANCIAL HEALTH OF LIFE INSURANCE COMPANIES USING RISK-BASED CAPITAL AND EARLY WARNING SYSTEM (Case Study on Life Insurance Companies in Indonesia 2014 - 2018) - Ariffin, Firzha Nur (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to assess the financial health of life insurance companies in Indonesia using a qualitative descriptive research method with a case study approach. The data used are secondary in the form of financial reports from 8 life insurance companies in Indonesia for 5 years from 2014 to 2018. The data obtained were analyzed using the Early Warning System (EWS) method including solvency ratio, level of fund adequacy, changes surplus, underwriting, claim expense, return on investment, liquidity, premium growth, self-retention and Risk-Based Capital (RBC) to see the company's financial performance during that period. Then the results are compared between one company and another. The results showed that there were significant differences between one company and another. This is indicated by the results of different ratio assessments and each company has its advantages and disadvantages during the 5 years of the study period. but some ratios have the same criterion value (meet the applicable rules), namely in terms of the Solvency ratio, the Fund Adequacy Level ratio.Â Keywords: Insurance Financial Performance, Early Warning System, Risk-Based Capital